The determinants of selection and allocation decisions for health assistance: Which role do health indicators play? - Katharina Stepping (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper analyzes the selection and allocation decisions of major and like-minded bilateral donors as regards development assistance for health for the period of 1990 till 2007. The central question is to what extent health indicators, reflecting the health objectives stated in the Millennium Development Goals, influence such decisions. The analysis reveals that health indicators are important determinants of the selection and allocation process for health assistance but to a different degree at the two stages; HIV prevalence is the proxy with the strongest impact. The results also show that the quality of the institutional environment and the bilateral relations affect the decisions of many donors. The national health expenditures, however, have no systematic effect and the allocation pattern of possible competitors is irrelevant for almost all donors. The evidence illustrates, furthermore, the great heterogeneity among major and like-minded donors as well as the differences between selection and allocation stage.
Keywords: F35; O15; O19; 330; Foreign aid; Assistance; Health; Aid policy; MDGs; Entwicklungshilfe; Ausländisch; Gesundheit; AIDS; Millennium Development Goals; Entwicklungsländer